Effectiveness of endobronchial coil treatment for lung volume reduction in patients with severe heterogeneous emphysema and bilateral incomplete fissures: a six-month follow-up - Kontogianni, Konstantina; Gerovasili, Vasiliki; Gompelmann, Daniela; Schuhmann, Maren; Heußel, Claus Peter; Herth, Felix; Eberhardt, Ralf (Respiration, 2014)
Background: Treatment with lung volume reduction coils (LVRC) may be effective in patients with severe heterogeneous emphysema and incomplete fissures. Objective: We hypothesized that LVRC placement improves pulmonary function, exercise tolerance and quality of life in these patients. Methods: Twenty-six patients with chronic obstructive pulmonary disease (COPD), 13 males and 13 females, aged 66 ± 8 years with heterogeneous emphysema and incomplete fissures were included in this retrospective analysis. The coils were implanted unilaterally in the upper or lower lobe. Patients were followed up at 30, 90 and 180 days after treatment and changes in pulmonary function test and 6-minute-walk-test (6MWT) values as well as scores for the modified Medical Research Council (mMRC) dyspnea scale and the St. George's Respiratory Questionnaire (SGRQ) were recorded. Results: FEV1 improved significantly at 90 days and tended to decrease at the 180-day follow-up (0.67 ± 0.17 vs. 0.78 ± 0.25 vs. 0.73 ± 0.21 liters, respectively, p < 0.001). The 6MWT score had improved significantly at 90 days and had tended to decrease at the 180-day follow-up (216 ± 107 vs. 262 ± 97 vs. 262 ± 112 m, respectively, p = 0.001). SGRQ was significantly improved at 90 days. Multivariate analysis showed that worse 6MWT performance at baseline was independently associated with a greater improvement in 6MWT at the 90-day follow-up. The total complication rate was 54% (n = 14) and included light hemorrhage in 6 patients, COPD exacerbation in 6, pneumothorax in 1 and both COPD exacerbation and pneumothorax in 1 patient. Conclusions: This is the first study to show that LVRC in patients with heterogeneous emphysema and incomplete fissures improves exercise capacity, quality of life and lung function up to 90 days after the intervention. Further studies are needed to assess the long-term effects of LVRC in these patients.
Gesehen am 29.09.2020